The centipede Strigamia maritima possesses a large complement of Wnt genes with diverse expression patterns. Issue 3 (23rd April 2014) - Hayden, Luke; Arthur, Wallace
SUMMARY The genes of the Wnt family play important roles in the development of many animals. In the arthropods, these genes are known to have multiple functions, including roles in posterior development and segmentation. Despite this, secondary loss of Wnt genes is common among the Arthropoda. Unlike many arthropods, Strigamia maritima, a geophilomorph centipede, possesses a large complement of Wnt ligands, with 11 Wnt genes present. In this study, the expression of each of these genes was examined across a range of stages during embryonic development. The expression of Wnt genes in Strigamia displays much variability. Most Wnt genes are expressed in segmental stripes in the trunk; near the proctodeum; and in the head region. However, despite this overall broad similarity, there are many differences between the various Wnt genes in their exact patterns of expression. These data should be considered in the context of different hypotheses regarding the functional relationships between the Wnt genes and the degree of redundancy present in this system. The findings of this study are consistent with one particular model of Wnt activity, the combinatorial model, whereby the combination of Wnt ligands present in a particular region defines its identity. These findings should also be useful in attempts to reconstruct the evolutionary history of Wnt signaling in arthropods.